The effect of return on assets (ROA) and debt to equity ratio (DER) on stock prices on insurance sub sector companies listed on the Indonesia stock exchange (IDX) period 2014-2018 - Ina Ratnasari; Ihsan Ramadhani (Department of Management, Universitas Malikussaleh, Aceh Utara, Indonesia, 2022)
Stock price is one of the factors that motivates investors to invest and is also a reward for the courage of investors to take risks for their investments. This study aims to determine the significant effect of Return On Assets and Debt to Equity on stock returns. The research sample used is the insurance sub-sector company on the Indonesia Stock Exchange for the 2014-2018 period, which amounted to 6 companies. Determination of the number of samples using a purposive sampling method, namely using the criteria in sampling. The data analysis technique used is multiple linear regression of panel data using Eviews 10 as data processing. Based on the results of the analysis, it was found that partially Return On had a positive and significant effect on stock prices, while the Debt to Equity Ratio had a negative and significant effect on stock prices. Simultaneously the results of the Return On Assets and Debt to Equity Ratio variables have an influence on stock prices.